INFLUENCE OF COMPOSITE RESIN ADHESIVE PROTOCOL ON NON-CARIOUS CERVICAL LESIONS ON SCLEROTIC DENTIN. SYSTEMATIC REVIEW. - Herrera Valdivia, Patricio Raúl (2021)
The amount of adult people around the world that present NCCL, is about 46,7% and with the growing trend of population aging, that condition has been growing last years, occurring frequently in the age group over 55 years. An important challenge for dentistry has been obtaining an adequate bond between the composite resin and the dentin, where it is still inaccurate around the junction in sclerotic dentin. It is necessary to contrast which protocol or adhesive technique provides an improvement in the adhesive-dentin interface, to achieve better adhesion of NCCL composite resin restorations on sclerotic dentin. This thesis project reviewed the literature on its way to find randomized clinical studies on adhesive protocols in composite resin restorations in NCCL on sclerotic dentin, by searching on MEDLINE/PUBMED, ELSEVIER/SCOPUS y WEB OF SCIENCE, hoping to identify the adhesive protocols that provide the best clinical behavior and longevity, presenting a surface treatment that improves the retention of composite resin restorations in NCCL with sclerotic dentin. 11 articles were studied meeting the standards established in this SLR. We conclude that there are techniques or protocols that have a very good influence adherence, where the vigorous application of adhesive systems and the pretreatment of the dentin with EDTA 15-17% for 1-2 minutes, increases the retention rates of the composite resin restorations in NCCL on sclerotic dentin.